2011
DOI: 10.1073/pnas.1110266108
|View full text |Cite
|
Sign up to set email alerts
|

CA1 neurons in the human hippocampus are critical for autobiographical memory, mental time travel, and autonoetic consciousness

Abstract: Autobiographical memories in our lives are critically dependent on temporal lobe structures. However, the contribution of CA1 neurons in the human hippocampus to the retrieval of episodic autobiographical memory remains elusive. In patients with a rare acute transient global amnesia, highly focal lesions confined to the CA1 field of the hippocampus can be detected on MRI. We studied the effect of these lesions on autobiographical memory using a detailed autobiographical interview including the remember/know pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
170
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(188 citation statements)
references
References 42 publications
16
170
0
2
Order By: Relevance
“…For example, humans with selective bilateral hippocampal damage sustained relatively early in life have a robust impairment in episodic memory, but show spared semantic memory [2]. Moreover, patients that develop acute, transient lesions of the HPC (specifically, area CA1) are amnesic for personal experiences with a flat retrograde gradient that extends decades into the past [5]. Accordingly, fMRI studies show that the HPC is involved in remembering personal experiences and the order in which they occurred on an autobiographical timeline [6,7].…”
Section: Introduction: the Hippocampus Is Critical To Remembering Expmentioning
confidence: 99%
“…For example, humans with selective bilateral hippocampal damage sustained relatively early in life have a robust impairment in episodic memory, but show spared semantic memory [2]. Moreover, patients that develop acute, transient lesions of the HPC (specifically, area CA1) are amnesic for personal experiences with a flat retrograde gradient that extends decades into the past [5]. Accordingly, fMRI studies show that the HPC is involved in remembering personal experiences and the order in which they occurred on an autobiographical timeline [6,7].…”
Section: Introduction: the Hippocampus Is Critical To Remembering Expmentioning
confidence: 99%
“…The hippocampus plays a key role in both the consolidation and the retrieval of memories, particularly episodic memory [34]. The hallucinations, which refer to retrieval function of memories, may be caused by inappropriate recollections from memory [35]. Several studies have demonstrated that several parietal regions are coherently spontaneously activated without task, stimuli, or explicit mnemonic demands, which suggest that these regions associated with the hippocampus can constitute a memory network [36].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also found site-specific (CA1 region) disturbances in hippocampal development following exposure to prenatal stressors [50,51,52]. The CA1 region of the hippocampus contains a high concentration of important efferent projections and pyramidal cells involved in processes such as memory and learning, which are known to be affected by exposure to prenatal stress [53,54,55]. Furthermore, this region of the hippocampus has also been shown to be selectively vulnerable to the deleterious effects of glucocorticoid exposure [56,57].…”
Section: Discussionmentioning
confidence: 99%